The Restorative Justice Orientation Regarding Sexual Violence Occurring in Religious-Based Educational Environments in Indonesia - Henny Saida Flora; Sahata Manalu; Nar Yan Thapa (Jurnal Dinamika Hukum, 2023)
Restorative Justice is a concept that focuses on victim recovery and is relevant to be applied in various regulations, one of which is the regulation for religious-based education in Indonesia. This study aims to answer two legal issues, namely the orientation of the application of the concept of Restorative Justice and the ideal formulation of the application of the concept of Restorative Justice to overcome acts of sexual violence in religious-based education environments. This research is a normative legal research with a concept and statutory approach. The results of the study show that the orientation of the concept of Restorative Justice in an effort to overcome acts of sexual violence in religious-based education environments already exists, such as the orientation to provide optimal recovery for victims. Even so, the concept orientation can still be considered partial or imperfect. Therefore, in order to perfect the arrangements regarding the concept of Restorative Justice, it is necessary to formulate an ideal by prioritizing two orientations, namely orientation to explicitly regulate the concept of Restorative Justice in laws and regulations as well as arrangements regarding the involvement of various sectors which include the surrounding community, foundation leaders, student guardians, to the School Committee to minimize sexual violence in religious-based education environments in Indonesia.Keywords: Religious Based Education; Restorative Justice; Sexual Violence.